(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2026)
High cholesterol levels are frequently thought to be connected with atherosclerosis. However, over the last 20 years, several studies have demonstrated that the pathophysiology of numerous diseases is significantly influenced by the buildup of excess cholesterol in different tissues and organs. Capsicum frutescens’ fruit extract shows Hypolipidemic activity in cholesterol-induced rats. To determine the Hypolipidemic characteristic of the active metabolites found in a fruit of Capsicum frutescens, an in silico docking is performed against six target proteins involved in the synthesis of cholesterol: acetoacetyl thiolase (PDB ID: 2F2S), HMG-CoA synthase (PDB ID: 2P8U), squalene synthase (PDB ID: 3V66, Oxido squalene cyclase (PDB ID: 1W6J), Niemann Pick C1 Like 1 (PDB ID: 6V3F), and 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoAR) (PDB ID: 3CDB).The molecular docking of the protein target is done using the PyRx software v8.0. The docking studies show that six target proteins strongly interact with a significant molecule, Ergosterol, with the highest binding affinity. Since Ergosterol can be used as a Hypolipidemic potential agent for further uses.